Epic Ramayana As A Medium for Teaching Indonesian Culture and Language: A Perspective of Darmasiswa Students - Dewi Yulianti, Ni Ketut (Institut Seni Indonesia Denpasar, 2020)
This paper discusses the epic Ramayana as a medium for teaching Indonesian culture and Indonesian language for the students of Darmasiswa RI / DRI (Darmasiswa of Republic of Indonesia). The epic Ramayana story contains adjective phrases as a media for teaching Indonesian culture which is full of the value of character education. This paper can be a reference for students and teachers who study and teach Indonesian culture and also Indonesian language for foreign speakers. Besides, it can also be beneficial for those who want to learn more about the structure of Indonesian language and character education of with the values of Indonesian culture in accordance with Ramayana text in which good character and personality become the main goal of national education in Indonesia. The research methodology statement is missing in this abstract. Considering that the Darmasiswa RI program is also part of education in Indonesia, the education of Indonesian character values cannot be separated from the education followed by Darmasiswa RI program participants. For this reason, there are two main points discussed in this paper, (1) the Ramayana text as a medium for teaching Indonesian culture and enhancing the mastery of Indonesian language and (2) the adjective phrase in the Ramayana text as a medium for the education of Indonesian character values. Theoretically and practically, this paper can contribute to the world of education both in terms of Indonesian culture and language and the noble values of Indonesian characters for foreign speakers, so that it can help in improving the success of national education, and also to improve the competitiveness of the nation.